The historicity of Kazakh genealogy story telling (zhyr). (Eurasian Journal of Philology Science and Education, 2019)
Genealogy storytelling (zhyr) that has survived until nowadays – is essential centuries-old oral historiography of Kazakh people passing from one generation to another, and telling about the developmentof Kazakh people as a coherent nation. Originally they were created in the form of genealogical tables(tree) of each clan, tribe, and then they were complemented by a variety of legends and stories whichwere transferred from grandparents to children, serving as a bridge between generations. Thus, this genrehas reached nowadays from the depths of the centuries, and has been transmitted from fathers to theirchildren as a testament to the descendants and can be reasonably attributed to the folklore heritage ofthe people and considered as an object of a scientific study. Kazakh folklore is replete with genealogystorytelling. National (historical) memory of Kazakh nation has been lingered until today mainly due togenealogy storytelling. This genre has not only kept in the memory, it has been also transformed into epicat some extent. The old genealogy tellers (shezhireshi) possess unique information on their family. It isevident that they know more than anyone else about their forefathers, outstanding personalities (batyr,poets, judges, orators, etc.). Genealogy, stories about great forefathers has being passed from generationto generation through legends and storytelling. The kazakh genealogy storytelling (zhyr) mentioned inthe article, has primarily taken as a subject of research